Depression and Dementia in Old-Old Population: History of Depression May Be Associated with Dementia Onset. The Tome Project - Liu, Yi-Chien; Meguro, Kenichi; Nakamura, Kei; Akanuma, Kyoko; Nakatsuka, Masahiro; Seki, Takashi; Nakaaki, Shutaro; Mimura, Masaru; Kawakami, Norito (Frontiers in Aging Neuroscience, 2017)
Background: In this study, we investigated the relationship among a history of depression, depressive states, and dementia in a community-based old-old cohort. Methods: From 2012 to 2013, we recruited 200 subjects residing in Tome, Japan. Ultimately, 181 subjects were enrolled in our study and completed the whole study protocol. We used the World Mental Health-Composite International Diagnostic Interview 3.0 to evaluate whether subjects had a history of depression or other affective disorders. Simultaneously, 3.0 Tesla brain magnetic resonance imaging was performed for each subject. Results: Of 181 subjects, 66 were normal (clinical dementia rating [CDR] = 0), 88 had MCI (CDR = 0.5), and 27 had dementia (CDR = 1 or above). Nine of the 181 subjects (4.9%) had a history of depressive episodes. CDR was significantly higher in subjects with a history of depression (0.9 vs. 0.4, p = .046) than in those without it. Seventy-two of the 181 subjects (39.7%) exhibited depressive symptoms. Subjects with depression exhibited lower Mini–Mental State Examination scores (21.6 vs. 23.3, p = .008), higher CDR scores (0.6 vs. 0.3, p = .004), and more atrophy of the medial temporal lobe (4.4 vs. 3.7, p = .036). Conclusion: A history of depression should be considered a risk factor for all-cause dementia. In the old-old population, depression is associated with a higher prevalence of dementia, lower cognitive performance, and a smaller hippocampus.